2016
DOI: 10.1177/1534734616671639
|View full text |Cite
|
Sign up to set email alerts
|

Wound Closure in Smoking Peripheral Arterial Disease Patients With Treatment-Refractory Ulcerations

Abstract: Despite ongoing smoking cessation efforts and optimized perfusion, failed wound closure in the presence of peripheral arterial disease (PAD) and diabetes are common. A clinical effectiveness review was conducted in actively smoking diabetic patients diagnosed with PAD, treated with serial applications of a viable intact cryopreserved human placental membrane (vCPM) (Grafix, Osiris Therapeutics Inc, Columbia, MD) for recalcitrant lower extremity ulcerations (n = 6). More than half of the patients were not candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The benefits of placental membrane, specifically amnion, have been reported in the literature for more than 100 years . vCPM retains the extracellular matrix, growth factors, and viable cells native to the placental membrane and can be used in the treatment of acute and chronic wounds of different etiologies and locations . In contrast, hFDS (Dermagraft ® ), a product that has been on the U.S. market since 2001, is a bioengineered skin substitute .…”
mentioning
confidence: 99%
“…The benefits of placental membrane, specifically amnion, have been reported in the literature for more than 100 years . vCPM retains the extracellular matrix, growth factors, and viable cells native to the placental membrane and can be used in the treatment of acute and chronic wounds of different etiologies and locations . In contrast, hFDS (Dermagraft ® ), a product that has been on the U.S. market since 2001, is a bioengineered skin substitute .…”
mentioning
confidence: 99%
“…20 Also in 2016, a retrospective review of five actively smoking diabetics with six nonhealing ulcers and peripheral arterial disease (PAD) who received serial applications of vCPM reported positive outcomes, as all patients achieved complete wound closure. 21 Further, Anselmo et al 22 showed positive clinical outcomes with vCPM in the treatment of three chronic wounds that had previously failed standard wound care treatments. These patients also had significant comorbidities including chronic heart failure, diabetes, peripheral vascular disease, and venous insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…One proprietary cryopreservation method developed by Osiris Therapeutics results in high cell viability within the preserved placental membrane and is a commercially available cryopreserved placental membrane product containing viable cells . Cryopreserved placental membrane (vCPM) retains the components of fresh placental membrane, and its clinical effectiveness has been demonstrated in various trials with hard‐to‐treat wounds using vCPM plus standard of care …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations